PENGARUH FINANCIAL DISTRESS, KARAKTERISTIK EKSEKUTIF, KOMISARIS INDEPENDEN, DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE - Anisa Tamara Madina; Indah Hapsari (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
Tax avoidance is an effort to reduce taxes legally which is carried out by making optimal use of provisions in the field of taxation, such as permitted exceptions and deductions as well as benefits or loopholes in other matters that have not been regulated and other weaknesses in the applicable tax regulations. This research aims to explain whether financial distress, executive characteristics, independent commissioners, and audit quality influence tax avoidance. The population used in this research are companies in the mining and plantation sectors listed on the Indonesia Stock Exchange in the 2017-2021 period. This research uses multiple linear regression tests. The results are: (1) financial distress has a negative effect on tax avoidance, (2) executive characteristics have no effect on tax avoidance, (3) independent commissioners have a positive effect on tax avoidance, (4) audit quality has no effect on tax avoidance. This indicates that companies experiencing financial difficulties tend to look for ways to reduce their tax burden, resulting in company cash savings in terms of corporate tax payments. The results of this research also indicate the importance of the existence of independent commissioners, who can supervise company tax management in order to minimize overly aggressive tax avoidance.